Kaustubha : souvenir of the diamond jubilee of the Kannada Literary Academy - Seetharamiah, Mysore Venkatadasappa, 1910- (Kannada Sahitya Parishat, 1977)
Comprises articles on the history, literature, arts and culture of Karnataka.